Correction: Reversible densification in nano-Li2MnO3 cation disordered rock-salt Li-ion battery cathodes. Issue 25 (17th June 2020) - Diaz-Lopez, Maria; Chater, Philip A.; Joly, Yves; Proux, Olivier; Hazemann, Jean-Louis; Bordet, Pierre; Pralong, Valerie
Abstract : Correction for 'Reversible densification in nano-Li2 MnO3 cation disordered rock-salt Li-ion battery cathodes' by Maria Diaz-Lopez et al., J. Mater. Chem. A, 2020, 8, 10998–11010, DOI: ; 10.1039/d0ta03372c .